Uncovering the molecular interplays of dopamine D1-like receptor activation - Tumova, Katerina (University of Ottawa (Canada), 2003)
D1-like dopaminergic receptor family consists of two heptahelical G protein-coupled receptors (GPCRs), termed D1A (or D1) and D1B (or D5). In this study, we have used a functional complementation of chimeric D1-like receptors to address the molecular interplay between the third extracellular loop (EL3) and the cytoplasmic tail (CT) in coordinating the functional properties of D1-like receptors expressed in transfected human embryonic kidney 293 (HEK 293) cells. Our results indicate that ED and CT participate in interfering intramolecular interactions that regulate the total functional receptor number and the agonist-mediated G protein coupling properties of the D1-like receptors in HEK 293 cells. In contrast, the agonist-independent activity of the D1-like receptors appears to be regulated solely by the sequences of the CT. In addition, we have identified the proximal region of CT, known as the fourth intracellular loop (IL4), as the pivotal domain underlying the CT-induced properties of the D1-like receptors. Overall, our study provides an insight into the molecular basis of D1-like receptor activation with possible implications for entire field of GPCR signaling.
Keywords: Biology, Molecular.; Biology, Neuroscience.